Private Monopolies and Public Rights - Hadley, Arthur T. (Quarterly Journal of Economics, 1886)
Journal Article Private Monopolies and Public Rights Get access Arthur T. Hadley Arthur T. Hadley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 1, October 1886, Pages 28–44, https://doi.org/10.2307/1883107 Published: 01 October 1886